2020
DOI: 10.1002/chem.201905408
|View full text |Cite
|
Sign up to set email alerts
|

Photoinitiated Thiol‐ene Reactions of Enoses: A Powerful Tool for Stereoselective Synthesis of Glycomimetics with Challenging Glycosidic Linkages

Abstract: Thioglycosides and C-glycosidesr epresent pharmacologically useful classes of glycomimetics that possess ah igh degree of biological stability. One emerging tool for the stereoselective synthesis of thioglycosides is the photoinitiateda ddition of thiols to unsaturated sugars. Moreover,t hiyl radical-mediated reactions of exo-glycals and 1-substituted endo-glycalso ffer facile routes to b-Cglycosidic structures. This Concepta rticle summarizes the thiol-ene coupling strategies developed recently by our group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 94 publications
1
40
0
Order By: Relevance
“…[100] 2-Acetoxyglycals, in turn, led stereoselectively to 1,2-cis-α-linked thiodisaccharides, which are difficult to obtain through other methods. Borbás [103] showed that many short cycles of Scheme 36. Free radical thiol-ene reaction with exocyclic double bonds, dr: diastereomeric ratios.…”
Section: Thiol-ene Reactions Through Radical Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…[100] 2-Acetoxyglycals, in turn, led stereoselectively to 1,2-cis-α-linked thiodisaccharides, which are difficult to obtain through other methods. Borbás [103] showed that many short cycles of Scheme 36. Free radical thiol-ene reaction with exocyclic double bonds, dr: diastereomeric ratios.…”
Section: Thiol-ene Reactions Through Radical Mechanismsmentioning
confidence: 99%
“…[102] It should be mentioned that Borbás recently published an excellent review which collects all the latest results on the photoinitiated thiol-ene reactions involving unsaturated sugars as precursors, portraying this method as a powerful tool for the construction of thiodisaccharides. [103]…”
Section: Thiol-ene Reactions Through Radical Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] In carbohydrate chemistry, the sugar moiety can be used both as a thiol or an alkene components, and such transformations show excellent regio-and stereoselectivities. 21 The hydrothiolation of exo-glycals allows the synthesis of novel, glycosylmethyl sulde (Gly-CH 2 -SR) type mimetics with very high or exclusive b-selectivity. [22][23][24][25] Based on the above experiences we set out to study the thiolene additions with various exo-mannals with the expectation that the b-stereoselectivity observed with other exo-glycal congurations will be maintained here as well.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that 1,2-cis-α-linked thioglycosides can be prepared with complete stereoselectivity by the photoinitiated, radical mediated thiol-ene coupling reaction (also known as a thio-click reaction) [11] of readily available 2substituted glycals. [12][13][14][15] The radical mediated thiol-ene coupling is known to proceed in a regioselective way to produce an anti-Markovnikov-type thioether, and in the case of substituted cyclic alkenes the addition occurs with high or complete stereoselectivity in a trans-diaxial manner via an axial attack of the thiyl radical onto the double bond followed by an axial hydrogen abstraction of the intemediate carbon-centered radical from the thiol. [13,15] Thus, the thio-click approach offers a simple and completely stereoselective way for the preparation of stable thio-linked analogues of the challenging 1,2-cis α-Oglycosides such as the sugar α-O-phosphates in UDP-sugars (Scheme 1A).…”
mentioning
confidence: 99%